INVITED EDITORIAL P.A.L.T.: An Interdisciplinary Model for Organizational Diagnosis and Intervention - Roberto Kertesz; Kertesz Víctor; Alicia Landau (European Scientific Journal, ESJ, 2017)
The present work is an analysis with comments of the model created by Dr. Roberto Kertész. The organization is a complex social reality that is defined as a set of people, a deliberate internal structure and a common goal. This is achieved through processes of transformation of certain "inputs" to the system - organization, obtained from the context or environment. The P.A.L.T is a systemic model, in which the organization has the opportunity to regulate its activity. The levels of the efficiency of the organizational performance will obviously depend on the quality of these interactions and the study of the nature of them will allow the management to achieve a set of more valuable results. In order to systematize this set of knowledge, it is convenient to group its components in a model that is both analytical and integral. The PALT model stands for this objective, which means the systemic integration of the Psychological, Administrative, Legal and Technical variables.